Telenomus remus (Hymenoptera: Platygastridae) parasitism on eggs of Anticarsia gemmatalis (Lepidoptera: Eribidae) compared with its natural host Spodoptera frugiperda (Lepidoptera: Noctuidae) - Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Bueno, Adeney de Freitas; Xavier, Maria Fernanda da Costa; Carvalho, Marina Mouzinho [UNESP] (Entomological Soc Amer, 2014)
The capacity of Telenomus remus to parasitize eggs of Anticarsia gemmatalis, compared with its natural host, Spodoptera frugiperda, was evaluated under different temperatures. The parasitoid T. remus was reared at 25 +/- 1 degrees C for a single generation on both hosts. After reaching the adult stage, they were allowed to parasitize both hosts to study parasitoid biology and parasitism capacity at temperatures between 19 degrees C and 37 +/- 1 degrees C. Egg-to-adult developmental time was similar on both hosts. The number of A. gemmatalis eggs parasitized was lower than that of S. frugiperda eggs at all temperatures. Parental female longevity of parasitoids was greater on A. gemmatalis eggs. This indicated a smaller metabolic expense during parasitism, a common feature observed on nonpreferable hosts. In general, sex ratio was little affected by temperature or hosts. When parental T. remus were reared on A. gemmatalis before the experiment, base temperature (Tb) and the thermal constant (K) were 9.53 degrees C and 209.57 DD on eggs of A. gemmatalis and 9.68 degrees C and 197.79 DD on eggs of S. frugiperda, respectively. When parental T. remus were reared on S. frugiperda eggs, Tb and K were 10.12 degrees C and 188.46 DD and 9.69 degrees C and 190.24 DD for the evaluated host eggs of A. gemmatalis and S. frugiperda, respectively. Therefore, T. remus develops in eggs of A. gemmatalis. This can be beneficial for its use in field crops where outbreaks of both Spodoptera spp. and A. gemmatalis occur. However, A. gemmatalis is a less favorable host for the parasitoid development.
Keywords: velvetbean caterpillar; biological control; alternative host; egg parasitoid; temperature